The recognition of Asplenium loriforme from Asplenium angustum (Aspleniaceae) based on morphology and distribution - Reis, Atiles; Lino, Vanessa; Mynssen, Claudine Massi; Sylvestre, Lana Da Silva (Phytotaxa, 2024)
We review the identification of Asplenium angustum, its type locality, and its occurrence as an endemic species from the Atlantic Forest of Brazil. To assess these matters, the itinerary of the Freyreiss expeditions through Brazil in 1814 is discussed. Based on the morphology of laminae and spores, we assume the plants from the Amazon Forest as a distinct species, one that should be recognized under the published name A. loriforme. Lectotypes are designated for A. angustum and A. serratum var. caudata.